Розробка та тестування системи MQTT-комунікації на Raspberry Pi - Цис, Роман Іванович (Луцьк : ЛНТУ, 2025)
У роботі проведено аналіз протоколу MQTT у IoT-архітектурах, порівняно популярні брокери та механізми безпеки (TLS, ACL, автентифікація). Обґрунтовано вибір апаратної платформи Raspberry Pi та клієнтів ESP32, сформовано програмно-апаратний стек із брокером Eclipse Mosquitto та Node-RED. Реалізовано побудову системи, налаштування брокера та сценарії обміну даними (телеметрія, керування, retained-повідомлення, LWT), проведено експерименти та надано рекомендації для безпечного та ефективного використання MQTT у локальних IoT-системах.

The study analyzes the MQTT protocol in IoT architectures, comparing popular brokers and security mechanisms (TLS, ACL, client authentication). The choice of Raspberry Pi as the platform and ESP32 client nodes is justified, with a hardware-software stack built using the Eclipse Mosquitto broker and Node-RED. The system setup, broker configuration, and typical data exchange scenarios (telemetry, control, retained messages, LWT) were implemented, experimental results obtained, and practical recommendations provided for secure and efficient use of MQTT in local IoT systems.
Development and testing of an MQTT communication system on Raspberry Pi
Keywords: Raspberry Pi; MQTT; Mosquitto